Sanitation Behavior Among Flood Disaster Victims In Bukittinggi City – West Sumatra - Putri Nilam Sari; Aria Gusti (Sriwijaya Journal of Environment, 2018)
Bukittinggi is one of city in West Sumatra that is potentially flooded and happen at the highest rainfall periods. Only three from 24 urban villages in Bukittinggi have low sanitation risk and it increases the flood-following disease. This research was done with quantitative approach to identified sanitation behavior among flood affected people as many as 47 respondents taken by proportional random sampling. The result showed the frequency distribution and percentage of each variable. Most flood-affected people in the Bukittinggi have toilets, but half of them use disposable diapers for their children and end up in trash cans. A small percentage of people dispose their waste water through toilets and their sewers are in poor condition. Most people do not segregate their solid waste and almost all of the solid waste have been dumped to the temporary dump site. Most people wash their hands with soap, but only small number do it before cooking. It is suggested to government to socialize the importance of sanitation and strengthen the role of community leaders to increase community awareness to have clean and healthy lifestyle.